(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Our main aim of the project is to know the causes and preventive measures of cracks in buildings. A crack is a complete or incomplete separation of concrete in two or more parts by breaking or fracturing. It is a inherent feature in concrete which cannot be prevented but controlled and reduced. Structural Cracks are a common occurrence in all types of buildings. To ensure the longevity of the structure, engineers are often required to look into their causes and carry out suitable repairs and remedial measures. For repairs and remedies to be effective, it is essential that the engineer should have a proper understanding of various causes of occurrence of cracks. For investigating the causes it is necessary to observe carefully the location, shape, size, depth, behavior and other characteristics of the cracks, and to collect information about specifications of the job and time of construction. It is also necessary for the engineer to keep track of when the cracks first came to notice.